Unlocking the synergy between intellectual capital and cost efficiency in Islamic bank - Hadi, T. Saipul; Laila, Nisful; Yatoo, Nissar Ahmad (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study examines the contribution of intellectual capital (IC) to Islamic banks’ cost efficiency.Methodology – The data envelopment analysis (DEA) method uses an intermediation approach to measure the cost efficiency of Islamic banks and modified value-added intellectual capital (MVAIC) as a measurement of IC. The sample of this research comprises 11 Islamic commercial banks registered with the financial services authority (Otoritas Jasa Keuangan, OJK) and operating from to 2014-2023. This research method uses the system generalized method of moments (SGMM) regression to analyze the impact of IC on the cost efficiency of Islamic banks. Findings – The results showed that IC positively affects the cost efficiency of Islamic banks in Indonesia. Another finding is that human capital (HC) contributes significantly to improving the cost efficiency of Islamic banks. structural capital (SC), capital employed (CE), and relational capital (RC) do not affect the cost efficiency of Islamic banks.Implications – This research implies that Islamic banks can determine which IC components require additional investment to improve efficiency and provide future Islamic banking performance-oriented towards new technology.Originality – This study seeks to fill the gap in previous research by analyzing the impact of IC and its components on the cost efficiency of Islamic banks.